Should competition policy in banking be amended during crises? Lessons from the EU - Iftekhar Hasan; Matej Marinc (Bank of Finland, 2013)
This article investigates the nexus of competition and stability in European banking. It analyzes the European legal framework for competition policy in banking and several cases that pertain to anti-cartel policy, merger policy, and state-aid control. It discusses whether and how competition policy should be amended in order to preserve the stability of the banking system during crises. The article argues for increased cooperation between prudential regulators and competition authorities, as well as an enhanced framework for bank regulation, supervision, and resolution that could mitigate the need to change competition policy in crisis times.
URN:NBN:fi:bof-20140807588
Keywords: G21; G28; K21; L40; 330; Banking; Competition Policy; Financial Crisis